Association of DNA repair gene polymorphisms with colorectal cancer risk and treatment outcomes - Al-Shaheri, Fawaz N.; Al-Shami, Kamal M.; Gamal, Eshrak H.; Mahasneh, Amjad A.; Ayoub, Nehad M. (Experimental and molecular pathology, 2020)
Colorectal cancer (CRC) is the third most common carcinoma worldwide. Despite the progress in screening and treatment, CRC remains a leading cause of cancer-related mortality. Alterations to normal nucleic acid processing may drive neoplastic transformation of colorectal epithelium. DNA repair machinery performs an essential function in the protection of genome by reducing the number of genetic polymorphisms/variations that may drive carcinogenicity. Four essential DNA repair systems are known which include nucleotide excision repair (NER), base excision repair (BER), mismatch repair (MMR), and double-strand break repair (DSBR). Polymorphisms of DNA repair genes have been shown to influence the risk of cancer development as well as outcomes of treatment. Several studies demonstrated the association between genetic polymorphism of DNA repair genes and increased risk of CRC in different populations. In this review, we have summarized the impact of DNA repair gene polymorphisms on risk of CRC development and treatment outcomes. Advancements of the current understanding for the impact of DNA repair gene polymorphisms on the risk and treatment of CRC may support diagnostic and predictive roles in patients with CRC.